Night sleep electroencephalogram power spectral analysis in excessive daytime sleepiness disorders - Rubens Reimão (Arquivos de Neuro-Psiquiatria)
A group of 53 patients (40 míales, 13 females) with mean age of 49 years, ranging from 30 to 70 years, was evaluated in the. following excessive daytime sleepiness (EDS) disorders : obstructive sleep apnea syndrome (B4a), periodic movements in sleep (B5a), affective disorder (B2a), functional psychiatric non affective disorder (B2b). We considered all adult patients referred to the Center sequentially with no other distinctions but these three criteria: (a) EDS was the main complaint; (b) right handed ; (c) not using psychotropic drugs for two weeks prior to the all-night polysomnography. EEG (C3/A1, C4/A2) samples from 2 to 10 minutes of each stage of the first REM cycle were chosen. The data was recorded simultaneously in magnetic tape and then fed into a computer for power spectral analysis. The percentage of power (PP) in each band calculated in relation to the total EEG power was determined of subsequent sections of 20.4 s for the following frequency bands: delta, theta, alpha and beta. The PP in all EOS patients sample had a tendency to decrease progressively from the slowest to the fastest frequency bands, in every sleep stage. PP distribution in the delta range increased progressively from stage 1 to stage 4; stage REM levels were close to stage 2 levels. In an EDS patients interhemispheric coherence was high in every band and sleep stage. B4a patients sample PP had a tendency to decrease progressively from the slowest to the fastest frequency bands, in¡ every sleep stage; PP distribution in the delta range increased progressively from stage 1 to stage 4; stage REM levels were between stage 1 and stage 2 levels. B2a patients sample PP had a tendency to decrease progressively from the slowest to the fastest frequency bands, in every sleep stage; PP distribution in the delta range increased progressively from stage 1 to stage 4; stage REM levels were close to stage 2 levels. B2b patients sample PP had a tendency to decrease progressively from the slowest to the fastest frequency bands, in every sleep stage; PP distribution in the delta range increased progressively from stage 1 to stage 3; stage 4 levels were close to stage 3 levels; stage REM levels were close to stage 2. B5a patients sample PP had a tendency to decrease progressively from the slowest to the fastest frequency bands, in every sleep stage; PP distribution in the delta range increased progressively from stage 1 to stage 3; stage REM levels were close to stage 2 levels, Interhemispheric coherences of B4a, B2b, and B5a groups were high in, every band and sleep stage. B4a, B2a, B2b, and B5a power spectral analysis comparison showed higher PP in B2b stage 1 alpha band, as well as, higher PP in B5a stage 2 theta band. The B4a versus. B2a power spectral analysis comparison showed higher PP in B4a stages 1 and REM alpha bands, as well as higher PP in B2a stage REM delta band.